THE INFLUENCE OF LEADERSHIP ON MOTIVATION OF JUNIOR SOCCER ATHLETES (Fiep Bulletin - online, 2015)
The aim of this study was identify the team lider and how his motivation can influence other athletes and the own team. It's known that psychology work has the objective to analyze changes in psychology training and modifications on process and psycho states (motivation and leader). The sample was composed by 48 male athletes from basic categories of Curitiba's soccer teams  age of 17,58 (1,27) years old. It's used 2 instruments of research for data collect: Leader Inventory and Psychometric properties of the Intrinsic Motivation Inventory in a competitive sport settting. Data were analyzed using a descriptive statistic and a variance analyze (p
Keywords: leader; motivation and soccer.